Bilayer Charge Asymmetry and Oil Residues Destabilize Membranes upon Poration - Leomil, Fernanda S C (Langmuir : the ACS journal of surfaces and colloids, 2024)
Transmembrane asymmetry is ubiquitous in cells, particularly with respect to lipids, where charged lipids are mainly restricted to one monolayer. We investigate the influence of anionic lipid asymmetry on the stability of giant unilamellar vesicles (GUVs), minimal plasma membrane models. To quantify asymmetry, we apply the fluorescence quenching assay, which is often difficult to reproduce, and caution in handling the quencher is generally underestimated. We first optimize this assay and then apply it to GUVs prepared with the inverted emulsion transfer protocol by using increasing fractions of anionic lipids restricted to one leaflet. This protocol is found to produce highly asymmetric bilayers but with ∼20% interleaflet mixing. To probe the stability of asymmetric versus symmetric membranes, we expose the GUVs to porating electric pulses and monitor the fraction of destabilized vesicles. The pulses open macropores, and the GUVs either completely recover or exhibit leakage or bursting/collapse. Residual oil destabilizes porated membranes, and destabilization is even more pronounced in asymmetrically charged membranes. This is corroborated by the measured pore edge tension, which is also found to decrease with increasing charge asymmetry. Using GUVs with imposed transmembrane pH asymmetry, we confirm that poration-triggered destabilization does not depend on the approach used to generate membrane asymmetry